The double‐edged sword of recombination in breakthrough innovation - Kaplan, Sarah; Vakili, Keyvan (Strategic Management Journal, 2015)
We explore the double‐edged sword of recombination in generating breakthrough innovation: recombination of distant or diverse knowledge is needed because knowledge in a narrow domain might trigger myopia, but recombination can be counterproductive when local search is needed to identify anomalies. We take into account how creativity shapes both the cognitive novelty of the idea and the subsequent realization of economic value. We develop a text‐based measure of novel ideas in patents using topic modeling to identify those patents that originate new topics in a body of knowledge. We find that, counter to theories of recombination, patents that originate new topics are more likely to be associated with local search, while economic value is the product of broader recombinations as well as novelty . Copyright © 2014 John Wiley & Sons, Ltd.